2017
DOI: 10.1080/13548506.2017.1338737
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of alcohol-metabolizing enzymes and their association with alcoholism risk, personality and anthropometric traits among Malaysian university students

Abstract: Three single nucleotide polymorphisms (SNPs) in alcohol-metabolizing genes - ADH1B (Arg47His), ADH1C (Ile350Val) and ALDH2 (Glu504Lys) have been extensively associated with flush reaction and alcoholism. Therefore, we investigated the association of these three SNPs with alcohol-induced reactions (AIRs), alcoholism risk, personality and anthropometric traits among Malaysian university students. AIRs, Self-Rating of the Effects of Alcohol (SRE) and Ten-Item Personality were surveyed, anthropometric measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The μ-opioid receptor (MOR) is a specific type of G-protein-coupled receptor that has a significant impact on reward and pleasure processes and has been associated with addictive behaviour [ 33 ]. This receptor has been found in the mesolimbic dopaminergic system of animal models, including in structures such as the basal ganglia and ventral tegmental area [ 34 , 35 ]. There is evidence suggesting that alcohol causes the release of endogenous opioids in the brain and indirectly activates opioid signalling pathways and that the rewarding effects and positive reinforcement experienced after alcohol consumption are regulated by opioid receptors [ 2 , 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The μ-opioid receptor (MOR) is a specific type of G-protein-coupled receptor that has a significant impact on reward and pleasure processes and has been associated with addictive behaviour [ 33 ]. This receptor has been found in the mesolimbic dopaminergic system of animal models, including in structures such as the basal ganglia and ventral tegmental area [ 34 , 35 ]. There is evidence suggesting that alcohol causes the release of endogenous opioids in the brain and indirectly activates opioid signalling pathways and that the rewarding effects and positive reinforcement experienced after alcohol consumption are regulated by opioid receptors [ 2 , 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that openness to experience is associated with certain genotypes and alleles of ADH1C and ALDH2 [ 35 ], but there have been no data about the correlation between the OPRM1 gene and personality traits up to now. Our data presented above are the first to prove that openness to experience may be related to OPRM1 gene polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in metabolism rate, compulsive alcohol use, altered behavior, and deleterious effects has been attributed to Single Nucleotide Polymorphisms (SNPs) occurrence in alcohol metabolizing genes in PAE fetuses and alcohol users (Ong et al, 2018;Katsarou et al, 2017). Non-synonymous SNPs (nsSNPs) comprise a group of SNPs that, together with SNPs in regulatory regions, are believed to have the highest impact on phenotype (Abid et al, 2023;Robert and Pelletier, 2018).…”
Section: Introductionmentioning
confidence: 99%